Penilaian Tingkat Kesehatan Bank Perkreditan Rakyat XYZ dengan Metode Camel (Periode 2017-2018) - Devi Rizka Sari; Destia Pentiana; Arif Makhsun (Jurnal Ilmiah ESAI, 2020)
This Final Task aims to find out the health level of people's credit banks in BPR XYZ in 2017 and 2018 by using the CAMEL method. This CAMEL method is based on the Decree of the Board of Directors of Bank Indonesia No. 30/12/KEP/DIR dated April 30, 1997 regarding the Procedures for Assessing the Health Level of The People's Credit Bank. The type of data used is secondary data in the form of bank management questionnaires that include general management and risk management and bpr xyz financial statements for the period 2017 - 2018. Data collection techniques are using documentation methods. The data analysis technique used is a quantitative analysis technique. The working procedure performed by the author is to calculate the ratio of each CAMEL component, calculate the credit score ratio and the credit score of factors, then sum up the entire credit score of factors and determine the category of BPR health predicate. The results of data analysis and discussion showed that the health level of BPR XYZ in 2017-2018 based on the CAMEL method received the title OF SEHAT.